The role of digitalisation in changing the business models in logistics: case of Ropax ports - Chen Yiran; Tsvetkova Anastasia; Edelman Kristel; Wahlström Irina; Heikkilä Marikka; Hellström Magnus (Slovenia, 2025)
This article explores digitalisation’s potential to change traditional business models in the context of RoPax (roll-on, rolloff passenger vessels) ports in four Northern European countries. The study examines digitalisation’s role in addressing business model change drivers, focusing on the perspective of port authorities (PAs). While digitalisation slowly affects operations at RoPax ports and PAs’ business models, the research data exhibits no radical business model innovation. Instead, the findings indicate that PAs introduce new digitalisation and business activities, potentially leading to business model renewal. However, the current digitalisation is inefficient, as technology providers lack an in-depth understanding of the port business and its ecosystem, and PAs have scarce knowledge of digitalisation’s business impact. The article concludes that connecting digitalisation strongly to the business model and strategic renewal is the way to overcome this challenge.
36th Bled eConference – Digital Economy and Society: The Balancing Act for Digital Innovation in Times of Instability